Efficient 3D placement of a UAV using particle swarm optimization - Shakhatreh H.; Khreishah A.; Alsarhan A.; Khalil I.; Sawalmeh A.; Othman N.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mobile telecommunication systems; Optimization; Particle swarm optimization (PSO); Tall buildings; Wireless networks; 3-D placements; Cellular network; Disaster situations; High rise building; Indoor path loss; Total transmit power; Wireless base stations; Wireless coverage; Unmanned aerial vehicles (UAV)